Heuristics for single machine scheduling problem with family setup times. (2017) - Peng, Yunfang; Han, Yajuan; Xiao, Yuyan; Ullah, Saif
Grouping of jobs from the same family on bottleneck resource is significant to reduce setup time of jobs. But, the grouping may result in delay of jobs. How to balance the contradiction between utilisation of bottleneck resource and delivery time is a great challenge in production scheduling. This paper considers a single machine scheduling problem in which each job to be scheduled belongs to a family and family setup times exist. This paper is aimed to identify a schedule of families of jobs to minimise total tardiness with respect to the given due dates of the jobs. A mathematical model is formulated for this problem and a heuristic solution approach is presented. Computational experiments show that the proposed heuristic algorithm performs better both in terms of solution quality and computational time.